FACTORS PREGNANT WOMEN WITH THE INCIDENCE OF PREECLAMPSIA AT PUSKESMAS KRESEK IN 2017 - Silfia Nuzulus Sa’idah; Solihati Solihati; Alni Sintapea; Ida Faridah (MOTORIK Jurnal Ilmu Kesehatan, 2019)
According to research, Mardiani and Neli 2013. It can be seen that mostrespondents with mother age > 35 years 13 people (76.5%) are at risk ofpreeclampsia and vice versa that is not as risky as 10 people (11,2), And inPuskesmas Kresek most of the respondents 39 people (72,2%) at risk ofpreeclampsia and 15 people (27,8) are not at risk. The purpose to find out thefactors of pregnant women with the incidence of preeclampsia in PuskesmasKresek 2017. The research methodology used descriptive correlation research.The population in this study were pregnant women with preeclampsia inPuskesmas Kresek Kabupaten Tangerang April 2017. Samples taken for thisstudy using total sampling that is as much as 54 people pregnant women withpreeclampsia. The method of data analysis using Chi Square test. In PuskesmasKresek the factors of pregnant women with preeclampsia incidence at risky areage (72.2%) were not at risk (27.8%), based on unresponsive parity (72.2%) andat risk (27.8% ), Based on a history of unresponsive pre-eclampsia (79.6%) andat risk (20.4%), based on risk-free obesity (61.1%) (38.9%), based on the resultsof risky blood pressure (68.5%) are not at risk (31.5%). The conclusion is thatthere is an age correlation with preeclampsia occurrence in p = 0,01 (p <0,05),no parity relation with preeclampsia occured in p value = 1.71 (p> 0,05), norelationhistoryPreeclampsiawiththeincidenceofpreeclampsiawasobtainedp=3.22 (p> 0,05), there was an association of obesity with the incidence ofpreeclampsia obtained p = 0,01 (p <0,05), there was correlation of bloodpressure result with incidence of preeclampsia In get value p = 0,00 (p =<0,05).